Hubungan Kondisi Sosial dan Fasilitas Terhadap Penggunaan Rekam Medis Elektronik di Instalasi Gawat Darurat Rumah Sakit X - Irda Sari; Novi Octaviani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Medical records are defined as written information that is accurately recorded about patient identity, patient complaints, disease and laboratory examinations, diagnosis, and treatment given to patients. An electronic system is used for medical records employees. The relationship between social conditions and facilities is very close and influences each other. The facilities available in a society play an important role in determining social conditions. The quantitative method of distributing questionnaires was used in this research. From distributing the questionnaires, 32 respondents obtained positive relationship results between Social Conditions and Facilities on the Use of Electronic Medical Records at Hospital X.